1996
DOI: 10.1039/cc9960002395
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies on ligand exchange at [IrH2Cl(CO)(PPh3)2] and [IrH2Cl(PPh3)3] by para-hydrogen induced polarisation

Abstract: Enhancement of NMR signals by para-hydrogen induced polarisation allows the rapid characterisation of [IrH2Cl-(CO)(PPh&] and [IrH2Cl(PPh3)3]: these complexes undergo ligand exchange via a 16-electron complex, [ IrH2C1(PPh3)2], which has a square-based pyramidal structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…For instance, in a simple 1 H NMR experiment, the maximum proton enhancement is achieved by the application of a π/4 (45 • ) pulse, instead of the conventional π/2 (90 • ) pulse. This, along with the other modifications necessary for more complex parahydrogen NMR studies, is described extensively in existing literature reviews, and in the original published reports of the pulse sequences [2,[13][14][15][16][17][18][19][20][21][22][23][24]. Among the advances detailed in these reports, it is particularly worth noting that methods have been developed which allow the parahydrogen-derived enhancement to be transferred to other nuclei by the use of appropriate NMR experiments, so that the characterisation of species by this approach is by no means restricted to 1 H nuclei alone.…”
Section: Experimental Considerationsmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, in a simple 1 H NMR experiment, the maximum proton enhancement is achieved by the application of a π/4 (45 • ) pulse, instead of the conventional π/2 (90 • ) pulse. This, along with the other modifications necessary for more complex parahydrogen NMR studies, is described extensively in existing literature reviews, and in the original published reports of the pulse sequences [2,[13][14][15][16][17][18][19][20][21][22][23][24]. Among the advances detailed in these reports, it is particularly worth noting that methods have been developed which allow the parahydrogen-derived enhancement to be transferred to other nuclei by the use of appropriate NMR experiments, so that the characterisation of species by this approach is by no means restricted to 1 H nuclei alone.…”
Section: Experimental Considerationsmentioning
confidence: 96%
“…The reaction of IrCl(CO)(PPh 3 ) 2 and the related complex IrCl(PPh 3 ) 3 with parahydrogen was investigated further by 2D NOESY methods [20,21]. These experiments revealed that, at 343 K, the intermolecular exchange of hydride ligands with free hydrogen was much more rapid in the case of IrCl(PPh 3 ) 3 than for IrCl(CO)(PPh 3 ) 2 .…”
Section: The Detection and Investigation Of Metal Hydride Speciesmentioning
confidence: 97%
“…[8]. For the initial conditions d(0) ϭ Ϫsin(⌬⍀ cat cat ), e(0) ϭ 0, and f(0) ϭ 0, the following time dependencies are obtained:…”
Section: Analysis Of the Influence Of The Catalystmentioning
confidence: 99%
“…Studies on the thermal addition of p -H 2 to a series of related complexes, (IrCl(CO)(PPh 3 ) 2 and RhCl(CO)(PPh 3 ) 2 ) have been previously reported. 19,20 These experiments yielded large PHIP enhancements for the iridium and rhodium dihydride products visible for tens of minutes, hence demonstrating the reversibility of H 2 addition and permitting signal averaging. Using both theoretical and experimental approaches, Bargon assessed the purity of the singlet state that is created between the hydride ligands of IrCl(H) 2 (CO)(PPh 3 ) 2 upon the addition of p -H 2 as greater than 50%.…”
Section: Introductionmentioning
confidence: 84%